PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS SAINTIFIK DENGAN APLIKASI CANVA PADA TEMA PERUBAHAN CUACA KELAS III SD - Ramadhani, Windy; Nurmairina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a product and determine the feasibility of a product and be able to find out student responses to scientific-based animated video media with the Canva application. This research also uses the Research and Development development model with the ADDIE model. The instrument used in this research is a questionnaire given to material expert validators, media experts, teachers and students. This research uses five stages, (1) Analysis stage, namely analyzing needs, media and material. (2) design stage, namely designing media according to needs. (3) development stage, which is making media according to the material that has been analyzed. The subjects in the study were material expert validators and media expert validators. Based on the results of the validation test, a percentage value of 95% from material experts and 88% from media experts was obtained. Which is where the percentage can be declared very valid / very feasible. (4). The implementation stage, namely testing the media directly to schools to get responses from teachers and students during learning. Based on the results of the data obtained from the teacher's response, the percentage score of 87% is categorized as very valid / very feasible and the student response of 19 students is at a percentage of 84% including in the feasible / valid category. While 6 other students are at a percentage of 16% included in the very valid category. These results state that scientific-based animated video learning media can provide new information, make it easier for students to understand the material, increase motivation, make it fun, and are easy to use. (5). The evaluation stage, at this stage it can be concluded that this scientific-based animated video media has very good quality and is feasible, so it can be used by teachers and students for learning.